Associations between Klinefelter's syndrome and autoimmune diseases: English national record linkage studies. (March 2015) - Seminog, Olena O.; Seminog, Alla B.; Yeates, David; Goldacre, Michael J.
Abstract There are reports suggesting that people with Klinefelter's syndrome (KS) may be at increased risk of some autoimmune diseases, but the evidence is not substantial. We wanted to add to the evidence by systematically assessing the risk of autoimmune diseases in a national cohort of people with KS. We selected records of all people with KS in a record-linked dataset of all hospital day cases and inpatient admissions in England, 1999–2011; and we followed them up by electronic record linkage to identify the occurrence of autoimmune diseases. We compared their occurrence in the KS cohort with a control cohort, studied in the same way, and expressed the results as rate ratios (RR). Of 30 autoimmune diseases studied in people with KS, there were significantly increased risks of seven–Addison's disease (RR 11.7, 95% confidence interval 2.4–34.4), diabetes mellitus type 1 (6.1, 4.4–8.3), multiple sclerosis (4.3, 1.2–11.0), acquired hypothyroidism (2.7, 1.8–4.0), rheumatoid arthritis (3.3, 2.0–5.2), Sjogren's syndrome (19.3, 4.0–57.0) and systemic lupus erythematosus (18.1, 2.2–65.6). We concluded that people with KS have increased risk of some autoimmune diseases, particularly those that are female-predominant. The increased risk of autoimmune diseases associated with the XXY karyotype may hold clues to the pathogenesis of some aspects of autoimmunity.